Aktivitas Pengungkapan Diri Remaja Putri Melalui Sosial Media Twitter - Ria Yunita (Universitas Bina Sarana Informatika, 2019)
Abstract -The phenomenon of self-disclosure, which is carried out by young women through Twitter is something interesting to study. Twitter becomes an online diary for most users, the term used in microblogs